Giant retroperitoneal myelolipoma: case report and literature review - Gunter Gerson; Maria P. F. G. Bêco; Carlos Gustavo Hirth; Maria do Perpétuo Socorro S. Cunha; Francisca Estefânia M. M. Lima; Francisco Victor C. Parente; River A. B. Coêlho (Sociedade Brasileira de Patologia Clínica, 2015)
Adrenal myelolipomas are unusual benign tumors with an average age of 60 years at onset, often associated with adrenal gland. A 63-year-old female presenting with abdominal discomfort and a large expanding mass in retroperitoneum occupying the right hemiabdomen, with extrinsic compression of adjacent organs, underwent tumor resection. Macroscopic examination of the surgical specimen showed a large yellowish homogeneous lesion with areas of hemorrhage, covered by a thin fibrous capsule. Microscopic analysis revealed a neoplasm composed of mature adipocytes permeated by hematopoietic tissue. There was residual adrenal cortex around the lesion.